EFFECT OF MINERAL, BIO-FERTILIZATION AND GROWING MEDIA ON GROWTH, FLOWERING AND CORMS PRODUCTION OF GLADIOLUS GRANDIFLORUS CV.''WHITE PROSPERITY'' PLANT - Mohamed Hassan; Ali El-Naggar; Mary Nasr; Mona El-Deeb (Scientific Journal of Flowers and Ornamental Plants, 2016)
This work was carried out in the Nursery of Floriculture, Ornamental Horticulture and Landscape Gardening Department, Faculty of Agriculture, Alexandria University, during the two successive seasons of 2010 and 2011. The aim of the present investigation was to evaluate the effect of growing media, mineral, and bio-fertilization on growth, flowering and corm production on Gladiolus grandiflorus L. cv. ''White Prosperity''. The experiment was a split-split plot design in three replicates, and forty-five treatments in each. The main plot represented the different growing media (GM1) 100% sandy soil, (GM2) 100% new reclaimed area (sandy-loam), (GM3) 50% sand + 50% peatmoss, (GM4) 50% sand + 50% New reclaimed area (sandy-loam) and (GM5) 50% New reclaimed area (sandy-loam) + 50% peatmoss. The sub-plot was the mineral fertilization NPK (19:19:19) which was used at three levels 50% NPK of recommended doses, 75% NPK of recommended doses and 100%NPK of recommended doses. The sub sub-plot represented bio-fertilizers [Nitrobine + Phosphorein 1:1 w/w] at rates (0.0, 5.0 and 10.0 g/plant). The best treatment due to these combination was occurred at GM3 (50% sand + 50% peatmoss) plus all levels of NPK combined with 5.0 and 10.0 g of biofertilizers/plant) on growth and flowering characteristics. GM5 (new reclaimed 50%+50% peatmoss) and GM3 (50% sand + 50% peatmoss) + 100% NPK +10.0 g/plant Nitrobine + Phosphorein gave the best result on corms production (corm volume and number of cormlets/plant). The best treatment was (GM3) + 100% NPK combined with the doses of bio-fertilizers )5.0 or 10.0 g/plant) gave the best result in leaf chlorophyll (a and b).